2022
DOI: 10.3390/jpm12081272
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Interventions for the Management of Oral Submucous Fibrosis: A Systematic Review and Network Meta-Analysis

Abstract: Introduction: Oral submucous fibrosis (OSMF) is a chronic premalignant condition and is characterized by fibroblastic change of lamina propria and stiffness of oral mucosa. Though there are several treatment options available, the best agent is not yet identified. This study assessed the comparative efficacy and safety of medical interventions in the management of OSMF. Methods: A systematic review was performed to identify randomized controlled trials (RCTs) that compared the efficacy of interventions for OSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…The intralesional injection of corticosteroids suppresses TGF-β1 and forms the mainstay in the treatment of OSF (Shih et al 2019 ). Nonetheless, none of the therapies have resulted in the successful treatment of OSF apart from rendering symptomatic relief to patients (Gopinath et al 2022 ). The standard treatment, corticosteroid injection reported side effects with higher chances of infection at the site of injection and systemic side effects such as adrenal insufficiency, edema, osteonecrosis, osteoporosis, myopathies and central serous chorioretinopathy, Hence, there is a need to identify an effective strategy for the treatment of OSF, which can be an alternative to the currently available treatment and provide symptomatic relief.…”
Section: Introductionmentioning
confidence: 99%
“…The intralesional injection of corticosteroids suppresses TGF-β1 and forms the mainstay in the treatment of OSF (Shih et al 2019 ). Nonetheless, none of the therapies have resulted in the successful treatment of OSF apart from rendering symptomatic relief to patients (Gopinath et al 2022 ). The standard treatment, corticosteroid injection reported side effects with higher chances of infection at the site of injection and systemic side effects such as adrenal insufficiency, edema, osteonecrosis, osteoporosis, myopathies and central serous chorioretinopathy, Hence, there is a need to identify an effective strategy for the treatment of OSF, which can be an alternative to the currently available treatment and provide symptomatic relief.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies included in the review did state that antioxidants were effective in managing OSMF, but the heterogeneity across the studies and the limited number of studies reported in the literature does not permit firm conclusions 12 . In contrast, another systematic review and network meta-analysis reported that Oxitard was the most effective compared to all other interventions in improving mouth opening among OSMF patients 25 . Though Oxitard has been shown to be effective in various studies, it also has some associated side effects.…”
Section: Dash Ks Et Al Herbal Alternatives In Early Stages Of Osmfmentioning
confidence: 91%
“…A prospective randomized controlled trial demonstrated significant improvement in the objective criteria like mouth opening, tongue protrusion, and relief from perioral fibrotic bands. Further, subjective criteria like a burning sensation in the mouth and difficulty in speech also recorded significant improvements 25 .…”
Section: Dash Ks Et Al Herbal Alternatives In Early Stages Of Osmfmentioning
confidence: 95%
“…In a network meta-analysis comparing the efficacy of different treatment interventions for OSF [80], most interventions were found to be superior to placebo in improving clinical symptoms, such as MMO and BS. Oxitard is superior to other interventions in improving MMO, aloe vera is superior in relieving BS, and lycopene has the lowest propensity for side effects and can be considered the best safety agent.…”
Section: Other Drugsmentioning
confidence: 99%